Study of Parameters Estimation of the Oral Glucose Tolerance Test Model with The Incretin Effects using Particle Swarm Optimization Algorithm. Issue 1 (March 2021) - Kartono, A; Restu, A A; Wahyudi, S T; Setiawan, A A; Irmansyah,; Sumaryada, T
Abstract: This study used the coupled ordinary differential equations to model the phenomenon of the results of the oral glucose tolerance test (OGTT). This research has two main challenges, such as (1) implementing the OGTT model with incretin effect and (2) estimating the present model parameters. Both challenges often make calculations difficult. The OGTT equations are formed by the coupled ordinary differential equations to describe the behaviour of the glucose-insulin dynamic system in the body. While the particle swarm optimization (PSO) algorithm is used as a tool to obtain parameter estimates of the ordinary differential equations effectively. This research proves that the PSO algorithm that has been applied to calculate the parameters is a simple and efficient method for the OGTT model with the incretin effect. The PSO algorithm is proven to be accurate, its accuracy is indicated by the R 2 value. The R 2 value of all simulations proved to be above 90%.